2019
DOI: 10.1136/sextrans-2019-053974
|View full text |Cite
|
Sign up to set email alerts
|

High willingness to use novel HIV and bacterial sexually transmitted infection partner notification, testing, and treatment strategies among gay and bisexual men

Abstract: ObjectivesWe sought to determine willingness of gay and bisexual men (GBM) to give HIV self-testing (HIVST) kits with patient-delivered partner therapy (PDPT) and engage in geosocial sexual networking (GSN) app-based partner notification.MethodsA nationwide sample of GBM who self-tested HIV negative (n=786) were asked about their willingness to give recent sex partners (main and casual) PDPT with an HIVST kit (PDPT+HIVST) after hypothetical bacterial STI (BSTI) diagnosis. Men were also asked about their willin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Social media or app-based innovations were evaluated in 33% (15/46) of studies [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] . Three studies assessed mobile HIVST-specific apps (7%, 3/46) [ 41 , 50 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media or app-based innovations were evaluated in 33% (15/46) of studies [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] . Three studies assessed mobile HIVST-specific apps (7%, 3/46) [ 41 , 50 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies assessed mobile HIVST-specific apps (7%, 3/46) [ 41 , 50 , 54 ]. Social media apps (e.g., Facebook, WeChat) and geospatial dating apps (e.g., Blued™, Grindr™) to promote HIVST were assessed in 26% (12/46) of studies [ 40 , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [51] , [52] , [53] ].…”
Section: Resultsmentioning
confidence: 99%
“…users are offered the referral) (35). As for overcoming the di culty of contacting casual partners, one option recommended by other studies-and suggested by MSM in our ndings as well-is geosocial networking app-based noti cation, which MSM have shown high willingness to use, particularly with an anonymous setting (36)(37)(38). Finally, a last consideration for the implementation of APNS in Mexico is that most of the states' criminal codes contemplate putting others at risk for infection as a crime (39); APNS should be implemented in all HIV/AIDS services to help avoiding potential legal cases.…”
Section: Discussionmentioning
confidence: 93%
“…However, the use of the opt-out referral in Mexico would have to be evaluated given the context of stigma and discrimination against HIV key populations. As for overcoming the difficulty of contacting casual partners, one option recommended by other studies—and suggested by MSM in our findings as well—is geosocial networking app-based notification, which MSM have shown high willingness to use, particularly with an anonymous setting [ 41 43 ]. Finally, a last consideration for the implementation of APNS in Mexico is that most of the states’ criminal codes contemplate putting others at risk for infection as a crime [ 44 ]; APNS should be implemented in all HIV/AIDS services to help avoiding potential legal cases.…”
Section: Discussionmentioning
confidence: 95%